2017
DOI: 10.17957/ijab/15.0370
|View full text |Cite
|
Sign up to set email alerts
|

Response of Soil Fungal Diversity to Nitrogen Deposition in a Deyeuxia augustifolia Wetland of Sanjiang Plain, Northeast, China

Abstract: In order to understand the effects of nitrogen deposition on soil fungal diversity, a study was conducted with a Deyeuxia augustifolia wetland in the Sanjiang Plain, China, using an experimental setup simulating nitrogen deposition at different loads over a five-year period. Three conditions were investigated: N1 (no artificial deposits, control), N2 with low-level nitrogen deposition (4 g N·hm -2 a -1) and N3 with high-level nitrogen deposition (8 g N·hm -2 a -1). At the end of the experiment the soil physioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
1
4
1
Order By: Relevance
“…The Glomeromycota phylum showed different responses of abundances in soils between the two types of communities, which can be an indicator of N addition to the wetlands of northeast China [69]. However, in our study, the change of Glomeromycota phylum abundance had a rare relationship with N uptake.…”
Section: N Availabilities In Two Communities With Contrasting Soil Ch...contrasting
confidence: 65%
“…The Glomeromycota phylum showed different responses of abundances in soils between the two types of communities, which can be an indicator of N addition to the wetlands of northeast China [69]. However, in our study, the change of Glomeromycota phylum abundance had a rare relationship with N uptake.…”
Section: N Availabilities In Two Communities With Contrasting Soil Ch...contrasting
confidence: 65%
“…Although we have no direct experimental measurements for the soil microbial activities, Garcia et al [55] have found that DHA is a good indicator of the status of soil microbial activity. Moreover, Sui et al found that High-N addition decreased soil fungal diversity and affected the fungal community composition and the relative abundance of species in the same experiment site and treatment [56]. Therefore, the alterations in the microbial community may also affect enzyme production and decomposer efficiency, and thus decrease respiration rate [23].…”
Section: Discussionmentioning
confidence: 99%
“…The soil of Sanjiang wetland showed weak acidity (5.21–5.31), and pH gradually decreased with N addition. Mou [ 67 ] and Sui [ 68 ] obtained similar results in a short-term N-application experiment.…”
Section: Discussionmentioning
confidence: 66%